2002
DOI: 10.1002/1522-2675(200203)85:3<841::aid-hlca841>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Titanium(IV) Bromide and Boron(III) Tribromide Promoted Baylis-Hillman Reactions of Arylaldehydes with But-3-yn-2-one

Abstract: The reaction of arylaldehydes with but-3-yn-2-one in the presence of the Lewis acids titanium(IV) bromide (TiBr 4 ) or boron(III) tribromide (BBr 3 ) (1.4 equiv.) can be drastically affected by the reaction temperature. When the reaction was carried out at À 208, the brominated compound 1 was obtained as the major product. However, when the reaction was carried out at room temperature (208), both the brominated compound 1 and dibrominated compound 2 were formed as major products. The substituent on the phenyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Shi and Wang also examined the reaction between but-3-yn-2-one with aryl aldehydes in the presence of TiBr 4 or BBr 3 . At −20 °C, β-bromo Baylis−Hillman adducts were formed with high E -selectivity (in the case of 2-(NO 2 )Ph and 3-(NO 2 )Ph, Z -selectivity is favored due to steric factors), whereas at room temperature dibromides 116 were obtained along with β-bromo Baylis−Hillman adducts (Scheme ).…”
Section: 3 Ticl4-mediated Baylis−hillman Reactionmentioning
confidence: 99%
“…Shi and Wang also examined the reaction between but-3-yn-2-one with aryl aldehydes in the presence of TiBr 4 or BBr 3 . At −20 °C, β-bromo Baylis−Hillman adducts were formed with high E -selectivity (in the case of 2-(NO 2 )Ph and 3-(NO 2 )Ph, Z -selectivity is favored due to steric factors), whereas at room temperature dibromides 116 were obtained along with β-bromo Baylis−Hillman adducts (Scheme ).…”
Section: 3 Ticl4-mediated Baylis−hillman Reactionmentioning
confidence: 99%
“…The far less reactive methyl prop‐2‐ynoate and HC≡C–CN gave β,β‐dibromo compounds 83 (Scheme ). Simultaneous research conducted by Li and co‐workers125b showed that the excesses of the ketone and TiBr 4 could be lowered to give “aldol adducts” 87 with various aldehydes, with excellent E selectivity and moderate yields. TiF 4 can also promote the MBH reaction, giving exclusively products of type 88 126…”
Section: Titanium(iv) Enolates In Morita–baylis–hillman Reactionsmentioning
confidence: 99%